2010
DOI: 10.1002/j.2333-8504.2010.tb02210.x
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence‐centered Approach to Using Assessment Data for Policymakers

Abstract: District‐level policymakers are challenged to use evidence of student achievement to make policy decisions, such as professional development and other school improvement plans. They currently receive reports of student achievement data that are complex, difficult to read, and even harder to interpret. Using the research literature on policymakers' use of data and conducting focus groups and interviews, we elicited information on their roles and responsibilities, as well as questions these people would like to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Other researchers (Hambleton & Pitoniak, 2006;Hambleton & Slater, 1997;Underwood, Zapata-Rivera & Van Winkle, 2010) also blame reports from national assessments for being complex, often couched in statistical jargon that users cannot decipher, difficult to read, and even more difficult to interpret. In South Africa, Kanjee and Moloi (2016) reported that, although the results of NAS had been considered in some policy-related decisions, there had been limited focus on using the results to support improvements in teaching and learning.…”
Section: Challenges To the Use Of Assessment Resultsmentioning
confidence: 99%
“…Other researchers (Hambleton & Pitoniak, 2006;Hambleton & Slater, 1997;Underwood, Zapata-Rivera & Van Winkle, 2010) also blame reports from national assessments for being complex, often couched in statistical jargon that users cannot decipher, difficult to read, and even more difficult to interpret. In South Africa, Kanjee and Moloi (2016) reported that, although the results of NAS had been considered in some policy-related decisions, there had been limited focus on using the results to support improvements in teaching and learning.…”
Section: Challenges To the Use Of Assessment Resultsmentioning
confidence: 99%
“…Although students are potentially proactive recipients of the feedback who bear the responsibility for actively responding to the feedback (Winstone et al, 2017), their engagement might be discouraged by several factors. Limited feedback literacy might account for students’ ineffective use of the feedback, especially when it contains complex jargons and abstract figures (Carless & Boud, 2018; Underwood et al, 2010; Zapata-Rivera et al, 2016). Worse, students’ unstated disagreement with and misunderstandings of the feedback might fail to be voiced by virtue of differential power relationships between teachers and students (Leighton, 2019).…”
Section: A Model Of Integrating National Standards In Local Contextmentioning
confidence: 99%
“…Each stakeholder group such as parents, teachers, administrators, and students are likely to have different needs for information, have different levels of pre-existing knowledge about the assessment and its context, and have different attitudes, feelings, or biases that might color their interpretations of the information shown in the reports (Zapata-Rivera and Katz, 2014). Results from Score Reporting research (e.g., Underwood et al, 2010;Kannan et al, 2021a) focused on specific stakeholder groups (e.g., parents, teachers, administrators) have highlighted the diverse needs, pre-existing knowledge, and attitudes for these groups.…”
Section: Audience Specificity In Score Reportingmentioning
confidence: 99%